The Effectiveness of Self-Compassion Training on Body Image Concern and Difficulties in Emotion Regulation in Women with Overweight - Safari , Zohre; Dinparast , Seyedeh Fatemeh; Salari, Mahdieh (Psychology of Woman Journal, 2026)
Objective: The present study was conducted to determine the effectiveness of self-compassion training on body image concern and difficulties in emotion regulation in women with overweight.Materials and Methods: This was a quasi-experimental study with a pretest–posttest design and a two-month follow-up including a control group. The statistical population consisted of women with overweight in Tehran in 2026. Overweight was defined based on a body mass index (BMI) ranging from 25 to 29.9. Following the initial screening, volunteer participants completed the Body Image Concern Questionnaire and the Difficulties in Emotion Regulation Scale. The mean score of the initial sample was 54.30 on the Body Image Concern Questionnaire and 106.40 on the Difficulties in Emotion Regulation Scale. Therefore, women who obtained scores above the mean on these two instruments were considered eligible for the intervention phase. Subsequently, 30 participants were selected through purposive sampling and randomly assigned to two groups: an experimental group and a control group, with 15 participants in each group. The experimental group received self-compassion training in eight 60-minute sessions, whereas the control group received no intervention during this period. Data were analyzed using the independent samples t-test, Fisher’s exact test, and two-way repeated measures analysis of variance in IBM SPSS Statistics.Findings: The results indicated that the experimental and control groups did not differ significantly in terms of demographic characteristics. Furthermore, the results of the two-way repeated measures analysis of variance demonstrated that the interaction effect of group and time on body image concern and difficulties in emotion regulation was significant. Based on mean comparisons, the scores of body image concern and difficulties in emotion regulation in the experimental group decreased from the pretest to the posttest stage, and this reduction remained largely stable at the two-month follow-up stage, whereas no substantial changes were observed in the control group.Conclusion: Based on the findings of the study, self-compassion training can reduce body image concern and difficulties in emotion regulation among women with overweight. Therefore, the application of this training in counseling centers, nutrition clinics, and psychological programs related to body image may be beneficial for improving women’s relationship with their bodies and enhancing their ability to manage difficult emotions.